Pedagogical conditions in the process of formation of сommunicative and strategic competence of the future primary school teachers - Mariia Oliiar (Vasyl Stefanyk Precarpathian National University, 2017)
The article is devoted the problem of forming communicative strategic competence offuture teachers of initial classes. The author reveals the content of pedagogical conditions offorming communicative strategic competence of future teachers. The author definesperspective directions of further research problems. Key words: future elementary school teacher, communicative-strategic competence,formation of communicative-strategic competence, pedagogical conditions.